Penerapan Model Project Based Learning (PJBL) Sebagai Upaya Meningkatkan Keterampilan Menulis Karangan Narasi Siswa Pada Pembelajaran Bahasa Indonesia Di Kelas III SD Negeri 1 Tataaran - Saldrak, Wanda Natalin; E. Rindengan, Mersty; Rorimpandey, Widdy (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2025)
This study aims to describe the implementation of the Project Based Learning (PJBL) approach to improve the writing skills of third-grade students at SD Negeri 1 Tataaran. The research category used was Classroom Action Research, which was implemented in two rounds, each of which included the design phase, implementation of activities, observation, and reflection. The research respondents were 27 third-grade students at Tataaran 1 Public Elementary School. The information gathering strategies applied included observation and evaluation, while the information analysis strategy used was descriptive analysis. Based on the learning achievement percentage obtained in the first cycle of 69.30%, improvements were needed in the second cycle, which subsequently indicated progress and achieved the classical mastery standard. Therefore, it can be concluded that the implementation of the Project Based Learning (PJBL) approach is effective in improving the writing skills of third-grade students at SD Negeri 1 Tataaran.